(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article investigates the integration of game-based learning in secondary school classrooms and the important teaching skills that support its efficiency. Through qualitative analysis of existing literature, case studies, and teacher experiences, the study classifies five key teaching competencies—instructional design, facilitation, assessment integration, adaptability, and emotional intelligence—as critical to the successful use of games for educational purposes. The findings suggest that when intentionally applied, game-based strategies can improve engagement, content mastery, and student collaboration. The paper also discourses implications for teacher training and future research directions.